Integrated Mobile Solar Cell-Based Nutrient Monitoring and Control System - Eliza; Heryanto (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
The rapid advancement of digital technology and the Internet of Things (IoT) has transformed the agricultural sector by enabling higher efficiency, precision, and sustainability through automation, sensor integration, and renewable energy utilization. This study presents the development of a Green Smart Hydroponic system powered by an 800 Wp solar photovoltaic unit and equipped with IoT-based monitoring to strengthen renewable energy and green technology education at SMK Negeri 1 Majalaya. Using a systems engineering approach combined with experimental testing, the system integrates solar panels, an ESP32 microcontroller, sensors for pH, TDS, and temperature, and an automatic nutrient pump to maintain optimal growing conditions. Field testing demonstrated stable system performance, consistently maintaining ideal hydroponic parameters including pH (5.07), TDS (1071 ppm), and temperature (24.1°C). The IoT-based real-time dashboard enhanced user accessibility and improved project-based learning outcomes for students by allowing direct observation of data-driven plant management. Findings indicate that the integration of renewable energy and IoT not only supports efficient hydroponic operation but also promotes environmental awareness and technological competence among vocational students. This research highlights the system’s potential as an effective educational tool that other schools can adopt to improve teacher competency, foster student engagement in green technology, and support the broader implementation of sustainable smart agriculture practices.